Motives of young basketball players for going in for sports - Budreikaite, A.; Macijauskas, K. (LASE Journal of Sport Science, 2015)
The aim of the research is to analyze the motives for going in for sports among young basketball players within the age group of 9-16 years. Research methods are as follows: analysis of relevant scientific research, questionnaire, and statistical analysis. Data was collected by cooperating with Silute Sports School upon receipt of consent; questionnaires were handed out to the pupils of the sports school. The research sample was composed of 100 respondents between the ages of 9 - 16 years attending Silute Sports School. The results of the present research identified and named the most common and significant motives encouraging the young basketball players to engage in sports across all age groups (interval of 10.16 years), which are the improvement of health and the possibility of making own sport-related achievements public. Considering different age groups, results demonstrate that boys at the age of 9 - 10 consider the following motives fundamental: to improve health and to express emotions. They believe that emotional enrichment when emotions experienced in sports come along with pleasure in doing such sports and appreciation of own achievements is highly significant. When it comes to the adolescents falling into the group of 11 - 12 year olds, willingness to compete, fight, and control oneself are the central motives, while to the adolescents at the age of 13 - 14 years it was to experience pleasure in sports, however, the group of 15 - 16 year olds name a possibility to become famous for sport-related achievements as the most significant motive.